Integration Of Character Education With Islamic Religious Education Subjects Based On School Culture - Agus Ruswandi; Muhammad Aditya Firdaus; Riki Ruswandi; Amir Supriatna (Institut Agama Islam An-Nawawi Purworejo, 2023)
Character education must be applied holistically in an educational institution, not only in the form of incidental activities utilizing cognitive learning or only through symbols. It is necessary to integrate holistic character values, one of which is in learning and through school culture. Strengthening character in elementary school students is not enough just with advice and lectures but must be made systematically with the learning process and activities at school. The purpose of this study is to describe the integration of character in school culture-based Islamic Religion Education learning. This research design used a qualitative design with purposive sampling at SD Darul Amal Jampangkulon, Sukabumi Regency. Data collection techniques were interviews, observation, and documentation. The results showed that the integration of character education was carried out by habituation and internalization of character in Islamic Religion Education learning based on 6 pillars of character. The integration of character education in Islamic Education based on school culture is proven to build better student character. This is evident from the results of the Sibanu questionnaire which shows the progress of students' character development while in the family environment.